2014
DOI: 10.1080/02699931.2014.886557
|View full text |Cite
|
Sign up to set email alerts
|

Gender of the expresser moderates the effect of emotional faces on the startle reflex

Abstract: It has been suggested that the impact of emotional expressions on the startle reflex is influenced by the intention communicated by the expression (e.g., the intention to attack). However, we propose that the meaning of an emotional expression is not only based on the intention, but is also influenced by characteristics of the expresser such as gender: since men are typically seen as more dominant than women, anger expressed by men should be perceived as particularly threatening, thus amplifying the startle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 28 publications
4
19
1
Order By: Relevance
“…With regard to expressions of sadness, although they are evaluated as more aversive than expressions of surprise, no significant differences were found in the physiological responses that were generated by sadness expressions compared with the other expressions. Similar results have been found for expressions of fear (Paulus et al, ; Springer et al, ). These results confirm the importance of the functional impact of emotional stimuli, in which activation of the defensive motivational system involves both the negative assessment of the stimulus and the degree of direct threat that is indicated by the stimulus.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…With regard to expressions of sadness, although they are evaluated as more aversive than expressions of surprise, no significant differences were found in the physiological responses that were generated by sadness expressions compared with the other expressions. Similar results have been found for expressions of fear (Paulus et al, ; Springer et al, ). These results confirm the importance of the functional impact of emotional stimuli, in which activation of the defensive motivational system involves both the negative assessment of the stimulus and the degree of direct threat that is indicated by the stimulus.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies that used threat and disgust pictures (i.e., human attacks, animal attacks, mutilation, and pollution) reported greater HR deceleration and an increase in the startle reflex in response to these types of stimuli (Bradley et al, ; Yartz & Hawk, ), indicating a greater attentional response and preparation for a fight/flight response, respectively. Different studies have found potentiation of the startle reflex in response to expressions of anger (Alpers et al, ; Anokhin & Golosheykin, ; Hess, Adams Jr., & Kleck, ; Hess, Sabourin, & Kleck, ; Paulus et al, ; Springer et al, ) because they indicate a direct threat to the observer. The present study extends this finding to expressions of disgust.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, pictures containing emotional faces have often been included in the broader category of emotional scenes (Lang & Greenwald, 1988). However, the effects of emotional facial expressions are not as distinct as the effects of emotional scenes (Alpers, Adolph, & Pauli, 2011; Paulus, Musial, & Renn, 2014). In addition, pictures of faces may vary in relevance to the observer based on head direction.…”
mentioning
confidence: 97%